2020
DOI: 10.1021/acs.chemrestox.0c00157
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cytotoxicity of Haloaromatic Disinfection Byproducts and Lead Co-exposures against Human Intestinal and Neuronal Cells

Abstract: Disinfecting drinking water with chlorine inadvertently generates disinfection byproducts (DBPs) which can cause potential adverse health effects to humans. Haloaromatic DBPs are a group of emerging DBPs recently identified, suspected to be substantially more toxic than haloaliphatic DBPs but have not been extensively studied. Simultaneously, service pipelines made of lead materials are widely used in water distribution systems and become a source of dissolved lead (Pb) in tap water. In this study, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…12 Iodophenols are toxic and carcinogenic. 9,13 In addition, to directly impact human health and the aquatic environment, odorous organic iodine would deteriorate aesthetic properties of drinking water, and they are precursors for the formation of I-DBPs. 6,14 I-DBPs are more cytotoxic and genotoxic than their chlorinated and brominated analogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Iodophenols are toxic and carcinogenic. 9,13 In addition, to directly impact human health and the aquatic environment, odorous organic iodine would deteriorate aesthetic properties of drinking water, and they are precursors for the formation of I-DBPs. 6,14 I-DBPs are more cytotoxic and genotoxic than their chlorinated and brominated analogs.…”
Section: Introductionmentioning
confidence: 99%
“…2,6-Diiodo-4-nitrophenol (up to 3.9 ng/L) and 2,4,6-triiodophenol (up to 0.43 ng/L) were detected in tap water in Yangtze River Delta of China . Iodophenols are toxic and carcinogenic. , In addition, to directly impact human health and the aquatic environment, odorous organic iodine would deteriorate aesthetic properties of drinking water, and they are precursors for the formation of I-DBPs. , I-DBPs are more cytotoxic and genotoxic than their chlorinated and brominated analogs. , Although investigations showed that organic iodine existed in natural waters and iodinated phenolic compounds would form in the disinfection of iodine-containing waters as DBPs, the possible existence of iodinated phenolic compounds in natural waters was ambiguous.…”
Section: Introductionmentioning
confidence: 99%